Sex-specific gene expression in the mosquito Culex pipiens f. molestus in response to artificial light at night. (December 2016) - Honnen, Ann-Christin; Johnston, Paul; Monaghan, Michael
Abstract Background Artificial light at night (ALAN) is a typical feature of urban areas and most organisms living in urban or suburban habitats are exposed to low levels of ALAN. Light is one of the most important environmental cues that organisms use to regulate their activities. Studies have begun to quantify the influence of ALAN on the behavior and ecology of organisms, but research on the effects at the molecular level remains limited. Mosquitoes in theCulex pipiens complex (Diptera, Culicidae) are widespread and abundant in urban areas where they are potential disease vectors. It is thus of particular interest to understand how ALAN may influence biologically and ecologically relevant traits. Results We used RNAseq to evaluate the transcriptome response in aCx. pipiens f. molestus laboratory population that was exposed to near-natural light conditions (light:dark L16:D8 hours, "control") and ALAN conditions with 3 h of constant low-level light at night (L16 + Llow 3:D5 hours, "low-light"). The resulting transcripts were mapped to the reference genome of the closely relatedCulex quinquefasciatus . Female expression patterns differed significantly between control and treatment conditions at five genes although none showed an absolute fold change greater than two (FC > 2). In contrast, male expression differed at 230 genes (74 with FC > 2). Of these, 216 genes (72 with FC > 2) showed reduced expression in the low-light treatment, most of which were related to gametogenesis, lipid metabolism, and immunity. Of the 14 genes (two with FC > 2) with increased expression, only five had any functional annotation. There was a pronounced sex-bias in gene expression regardless of treatment, with 11, 660 genes (51 % of annotated genes; 8694 with FC > 2; 48 % of annotated genes) differentially expressed between males and females, including 14 genes of the circadian clock. Conclusion Our data suggest a stronger response to artificial light by males ofCx. pipiens f. molestus than by females, and that a wide range of physiological pathways may be affected by ALAN at the molecular level. The fact that differences in gene expression appear to be sex-specific may have a strong influence at the population level.